(untitled) - Lougheed, Lin (White Plains, NY, 2007)
Longman Preparation Series for the New TOEIC® Test: Advanced Course, Fourth Edition, gives students the skills, strategy, practice, and confidence they need to increase their scores on the new TOEIC® test. Ideal for a TOEIC® test preparation course or for self-study, the Advanced Course is intended for students who achieve TOEIC® test scores from 450 to 850.
Keywords: Test of English for International Communication,English language,English language,Kiểm tra tiếng anh giao tiếp quốc tế,Tiếng anh; Examinations,Examinations,Sự thi tuyển